Gambaran Efikasi Diri Mahasiswa Santri Penghafal Al-Qur’an - Noor, Hana Nabila; Pihasniwati, Pihasniwati (Jurnal Psikologi Integratif, 2023)
College students who memorize al-qur’an are expected to have high self-efficacy because memorizing al-qur’an requires a long process and takes a long time. This study aims to explore and to understand self-efficacy of college students who memorize al-qur’an and to explore what factors influence their self-efficacy. This qualitative research used phenomenological approach with three participants. The data analysis used is an explication technique. The results showed three participants have strong self-efficacy. The three participants interpret the process they need to face during memorizing Al-Qur’an and following academic schedule as a challenge that must be completed. They managed their activities well, as well as they have successfully mastered various tasks. One participant focused on maximizing the process of memorizing al-qur’an and following academic schedule, while two other participants were maximizing their process in memorizing al-qur’an, following the lecture and also joining the organization. Three participants have also good confidence in their own ability to complete their target in memorizing al-qur’an and their study as well. Factors that influenced their self-efficacy are included their previous achievements, motivation to seek knowledge and emulating the success of others, and parental support. Mahasiswa yang menghafal al-qur’an diharapkan memiliki efikasi diri yang tinggi karena menghafal al-qur’an membutuhkan proses yang panjang dan membutuhkan waktu yang lama. Penelitian ini bertujuan untuk menggali dan memahami efikasi diri mahasiswa penghafal al-qur’an serta menggali faktor-faktor apa saja yang mempengaruhi efikasi diri mahasiswa tersebut. Penelitian kualitatif ini menggunakan pendekatan fenomenologis dengan tiga partisipan. Analisis data yang digunakan adalah teknik eksplikasi. Hasil penelitian menunjukkan tiga partisipan memiliki efikasi diri yang kuat. Ketiga partisipan memaknai proses yang harus mereka hadapi selama menghafal al-qur’an dan mengikuti jadwal akademik sebagai tantangan yang harus diselesaikan. Mereka mengatur kegiatannya dengan baik, mereka berhasil menguasai berbagai tugas. Satu partisipan fokus memaksimalkan proses menghafal al-qur’an dan mengikuti perkuliahan, sedangkan dua peserta lainnya memaksimalkan proses menghafal al-qur’an, mengikuti perkuliahan dan juga berorganisasi. Tiga partisipan juga percaya diri dengan kemampuan mereka sendiri untuk menyelesaikan target mereka dalam menghafal al-qur'an dan studi mereka. Faktor-faktor yang mempengaruhi efikasi diri mereka meliputi prestasi sebelumnya yang telah diraih, motivasi mencari ilmu dan meniru keberhasilan orang lain, dan dukungan orang tua.